Governance And Digital Transformation: Analisis Ruang Kerja Virtual Melalui Perspektif E-Government Pada Pemerintahan Provinsi Bali - Ni Putu Kartika Cahyani; I Putu Adi Permana Putra (Public Administration Dept, Faculty of Social and Political Science, 2024)
Digital transformation in the government sector is a form of public service innovation. Since the COVID-19 pandemic, various digital-based innovations have emerged as solutions to the problems that occur. This effort was made to provide services to the community during the pandemic. One of them is the presence of a virtual office as a work space platform that supports efficiency in providing public services. Virtual offices are a manifestation of an electronic-based government system (SPBE), administering government by utilizing technology, information, and communication. This system exists to realize effective, efficient, transparent, and accountable government governance. This article focuses on reviewing virtual offices as a digital-based public service from an e-government perspective. The study uses a qualitative descriptive approach with data collection techniques through literature studies, such as books, journal articles, websites, and other documents related to the research topic. The results of this research show that virtual offices are a form of government governance through digital transformation. A review from an e-government perspective shows that this system has demonstrated key elements in achieving successful e-government implementation. Among them are support, capacity, and value. Apart from that, the concept of dynamic governance shows that the virtual office is a form of transformational government governance that is able to answer the challenges of technological and information development. This supports dynamic government towards good governance.